Food matrix structure (from Biscuit to Custard) has an impact on folate bioavailability in healthy volunteers - Buffière, Caroline; Hiolle, Manon; Peyron, Marie-Agnès; Richard, Ruddy; Meunier, Nathalie; Batisse, Cindy; Rémond, Didier; Dupont, Didier; Nau, Françoise; Pereira, Bruno; Savary-Auzeloux, Isabelle (European journal of nutrition, 2021)
Purpose We examined the impact of matrix food structure on post-prandial folate bioavailability (and other macronutrients) in human volunteers using a randomized, controlled, crossover experimental design. Methods Twelve healthy male volunteers (22.6 ± 0.4 years old) were offered four food models (differing in matrix structure: Custard, Pudding, Sponge cake and Biscuit) to which 1 mg of folic acid was added, according to a randomized, controlled, crossover experimental design. Plasma folates, glucose, insulin, alpha amino nitrogen and triglycerides were measured over the post-prandial period (from T0 to T480 min). Results Food matrix structure was capable of altering folate plasma availability. The highest folate availability was observed for pudding and to a lesser extent Sponge cake whereas the lowest was for the two matrices presenting extreme rheological properties: Custard (liquid) ( P < 0.05 total AUC) and to a lesser extent Biscuit (hard solid) ( P < 0.05, AUC 180 min). The analysis of plasma kinetics of appearance of other nutrients/metabolites helps to understand/explain the lower bioavailability of folates in Custard and Biscuit. Conclusion A least overall efficient bio-accessibility of all macronutrients and folic acid is observed in the gut lumen for Biscuit (delayed/incomplete destructuration of biscuit along the digestive tract). On the contrary, the lower folic acid absorption observed with custard does not fit with the rapid plasma appearance of other nutrients and should require further investigation.